New frontiers in resistance breeding for nematode, Fusarium and sigatoka: Proceedings of a workshop, 2-5 October 1995, Kuala Lumpur, Malaysia - Frison, Emile A.; Horry, J-P.; Waele, D. de; International Network for the Improvement of Banana and Plantain (1996)
Proceedings of the workshop divided in three session: 1) Opportunities for conventional breeding for resistance to nematodes of banana and plantain; 2) Current approaches and future opportunities for improving major Musa types in Asia/Pacific regions; 3) Banana research in Malaysia. INIBAP / CIRAD / MARDI